High‐Performance and Ultra‐Stable Aqueous Supercapacitors Based on a Green and Low‐Cost Water‐In‐Salt Electrolyte. Issue 21 (5th November 2019) - Guo, Junhong; Ma, Yalan; Zhao, Kun; Wang, Yue; Yang, Baoping; Cui, Jinfeng; Yan, Xingbin
Abstract: The emergence of "water‐in‐salt" carbon‐based supercapacitors presents great potential for further improving the energy density, owing to the extended electrochemical stability window. However, not only low conductivity and high viscosity hinder the superior rate performance, but also the high cost of salts limits their commercialization. Here, we report a low‐cost concentrated sodium nitrate electrolyte for high‐performance and ultra‐stable supercapacitors, based on good electrochemical stability, high conductivity, and low viscosity. In the wide operation voltage range of 0–2.1 V, the constructed symmetric supercapacitor based on commercial active carbon exhibits a high specific capacitance of 32.68 F g −1 at 1 A g −1 . Moreover, superior rate capability (83 % capacitance retention from 1 to 20 A g −1 ) and excellent cycle stability (90 % capacitance retention after 9000 cycles) are also demonstrated. Consequently, this electrolyte system could be the most attractive candidate for promising carbon‐based supercapacitors to further improve the energy density. Abstract : Attractive solution : A low‐cost 12 m NaNO3 water‐in‐salt electrolyte is reported for high‐performance and ultra‐stable supercapacitors. The electrolyte offers good electrochemical stability, high conductivity, low viscosity, and weak corrosion, which leads to a remarkable specific capacitance and excellent rate capability at a high operation voltage of 2.1 V.